Influence of education on maternity care in the selected districts of Nepal. - Dhakal, Megha Raj (2010)
ABSTRACT: The primary objective of the study was to assess the current status of the use of maternity care services by women aged 15-49 years in the five selected districts of Nepal. Both the quantitative and qualitative mixed research methods were used to collect and process data. Quantitative data were used for testing hypothesis formulated in this study while qualitative pieces of information were used to supplement information to highlight some of the underlying factors associated with the utilization of maternal and child health care (MCH) services. Moreover, psychometric test, inter disciplinary approach and the use of both quantitative and qualitative pieces of information were used to explore the level of attitude and perception of the pregnant women towards households head and service providers. In addition to these factors, 14 new variables were constructed under the heading of empowerment, equity, satisfaction, plan for maternity care and responsibility of mother through factors analysis. A cross-sectional research design was adopted to carry out the study to examine linkages between formal and non-formal/ informal education and utilization of maternity care services. A sample of 384 women aged 15-49 years who had at least one live birth in the last three years from Sindhupalchok, Syanga, Kathmandu, Banke and Kailali districts was randomly selected. A structured questionnaire was used to interview women from within the sample utilizing interview guidelines. Besides descriptive analysis, bivariate analysis and logistic regression analysis were used o interpret the data to draw conclusions and recommendations. The finding of the study revealed that the place of residence, mother's education, recreational programs, level of income, the visit to a health facility for other medical problems, the age of mothers at child birth, the number of children, awareness about the use of family planning methods as well as cost coping strategy of the pregnant women have strong association with maternity care services. Education has a strong association with all seven variables and very strong net association with the use of antenatal care visits during pregnancy, the use of ANC package and the use of postnatal care services. Parenting skills transferred to the pregnant women by service providers, life-style adopted by the pregnant women, household environment properly managed by household head, satisfaction of pregnant women on pregnancy care preparation, care givers behaviors towards pregnant women, household head's willingness to monitors pregnancy status were associated with MCH services. The study concluded that mother's education is necessary but not a sufficient condition for maternity care. Therefore, the increases the use of MCH services. The study has a clear indication that program targeted to improve the education of women, income generating activities, as well as support of other family members on pregnancy and delivery care management, nearest distance of a health facility, placement of medical doctors especially outside Kathmandu Valley help to improve the use of maternity care services. The study also has recommended that a follow-up study designed to use the path analysis for analyzing effects of the distance and the intermediate factors used in the conceptual framework would be useful. The study providers a new knowledge about how formal and non-formal/informal education has influenced the utilization of maternity care services, the changes in reproductive behavior and the increase in the access to and utilization of available health care services.